2021
DOI: 10.11591/ijai.v10.i1.pp184-190
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer prediction model with decision tree and adaptive boosting

Abstract: In this study, breast cancer prediction model is proposed with decision tree and adaptive boosting (Adboost). Furthermore, an extensive experimental evaluation of the predictive performance of the proposed model is conducted. The study is conducted on breast cancer dataset collected form the kaggle data repository. The dataset consists of 569 observations of which the 212 or 37.25% are benign or breast cancer negative and 62.74% are malignant or breast cancer positive. The class distribution shows that, the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 12 publications
(16 reference statements)
0
30
0
1
Order By: Relevance
“…Iterative feature elimination removes irrelevant features that mislead the model's predictive capability and ultimately reduce the performance of classification model [20], [23]. Moreover, with reduced feature, the computational time required for model training and storage space requirement is optimized [22], [24]. The input features in the heart disease dataset employed in in training are shown in Table 1.…”
Section: Iterative Feature Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative feature elimination removes irrelevant features that mislead the model's predictive capability and ultimately reduce the performance of classification model [20], [23]. Moreover, with reduced feature, the computational time required for model training and storage space requirement is optimized [22], [24]. The input features in the heart disease dataset employed in in training are shown in Table 1.…”
Section: Iterative Feature Eliminationmentioning
confidence: 99%
“…As demonstrated in Table 5, the proposed model outperforms compared to the existing work. [5] 2019 NB, RF 86.81% Wan Hajarul [6] 2018 DT and RF 82.99% with RF Amin Ul Haq [8] 2018 SVM, DT, RF, NB, DT 86% with SVM Kathleen H. Miaoa [11] 2018 Deep neural network 83.67% Wiharto Wiharto [12] 2019 Ensemble classifier 88.33% Noor Basha [18] 2019 KNN, NB, SVM, DT 85%, with KNN Edsel Ing [19] 2019 SVM and LR 82.71% with LR Márcio Dias [20] 2020 SVM 87.71% Khaled Mohamad [21] 2020 SVM, NB 84.19% with SVM Pooja Rani [22] 2021 NB, LR, NB, SVM, RF 84.79% with SVM Suja Panicker [23] 2020 SVM 90% G. Magesh [24] 2020 RF 89.30% Ashir Javeed [25] 2020 Deep neural network 91.83% G. Saranya [ A hybrid approach to medical decision-making: diagnosis of heart disease … (Tamilarasi Suresh) 1837 5. CONCLUSION Automated intelligent approaches are crucial for timely prediction of heart disease.…”
Section: Comparative Studymentioning
confidence: 99%
“…Feature selection is important to enhance the classification accuracy of the predictive accuracy of a model for breast cancer prediction. Assegie et al [12], the researchers have suggested that, the performance of decision tree, adaptive boosting model greatly improves when the model is trained on optimal input feature. Moreover, optimal feature selection is significant to get insights into dataset and discover important feature from breast cancer dataset.…”
Section: Literature Surveymentioning
confidence: 99%
“…In another study [11], a model for chronic kidney disease detection is developed using an ensemble method. The model is implemented using decision tree algorithm and J48 supervised learning algorithm as base classifier and adaptive boosting as ensemble classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the challenge in identification of chronic kidney disease, the disease has become one of the world's deadliest diseases. The report shows that there are roughly 2.5 to 11.25 million cases chronic kidney disease worldwide [2][3][4][5][6][7][8][9][10][11][12][13]. Different machine learning algorithms such as support vector machine (SVM) [2] and boosting classifiers [4] are applied to kidney disease data repository to create predictive model with acceptable level of accuracy to identify chronic kidney disease as early as possible.…”
Section: Introductionmentioning
confidence: 99%